Supervisor support and affective organizational commitment: the mediator role of work engagement - Orgambidez, Alejandro (2021)
The aim of the study was to verify the mediator role of work engagement between supervisor social support and affective organizational commitment. A cross-sectional and correlational study using questionnaires was conducted. We obtained a convenience sample of 267 participants from 403 nurses from two public hospitals (66.25% response rate). Participants were required to be registered nurses without a supervisor position and to have worked for at least 1 year in the same ward in a public hospital. The mediator role of work engagement was examined using path analysis and bootstrapping method (bias-corrected confidence intervals). Results showed that affective organizational commitment was positively and significantly predicted by supervisor support, vigor, and absorption. Supervisor support had both a direct effect and an indirect effect, through vigor and absorption, on affective organizational commitment. Social support from supervisors allows an increase both in nurses' engagement and their desire to remain in the organization.